Closer [videorecording (DVD)] - Nichols, Mike; Roberts, Julia, 1967-; Law, Jude, 1972-; Portman, Natalie, 1981-; Owen, Clive; Marber, Patrick, 1964- (Sony Pictures Home Entertainment, 2005)
Dan, an aspiring novelist, cannot help but feel immensely attracted to Alice, a young American waitress and stripper who is in London after escaping from a failed relationship. The two meet after Alice is involved in a car accident. But nothing last forever, and after some time Dan meets Anna, a photographer, and he feels attracted to her. Nothing happens right away, but once it does, things go downhill for Alice and Dan. The two don't break up, but Dan is already mentally involved in the relationship. He is too much of a coward to leave Alice, even though he knows that Anna won't go out with him. Dan is so obessed with Anna that he even paves the way for the meeting between Anna and her future husband, Larry. Eventually Dan, Alice, Anna and Larry take part in a twisted dance of deceit, guilt and anger.